2015 UNFCCC Paris summit : India's dilemma - Shobhane, Gaurav; Jain, Bhaumik; Anchalia, Gautam; Agrawal, Ayush; Garg, Amit ([London] : SAGE, 2016)
In December 2015, 196 countries met in Paris to reach a new global climate change agreement. This case looks at the climate negotiation process from the eyes of India's environment minister, Mr Prakash Javadekar.
Originally Published in: Shobhane, G., Jain, B., Anchalia, G., Agarwsal, A., & Garg, A. (2015). 2015 UNFCCC Paris Summit - India's Dilemma. PSG0121. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; United Nations Framework Convention on Climate Change (Organization); Social responsibility of business -- Case studies; Climate change mitigation -- International cooperation -- Case studies; Environmental protection -- India -- Case studies